A cross-sectional survey of current treatment and symptom burden of patients with COPD consulting for routine care according to GOLD 2014 classifications - Ding B (International Journal of COPD, 2017)
Bo Ding,1 Mark Small,2 Ulf Holmgren3 1Medical Evidence and Observational Research, AstraZeneca Gothenburg, Mölndal, Sweden; 2Real World Research (Respiratory), Adelphi Real World, Bollington, UK; 3Global Payer Evidence and Pricing, AstraZeneca Gothenburg, Mölndal, Sweden Background: As part of the Respiratory Disease Specific Program (DSP) conducted to provide observations of clinical practice from a physician and matched patient viewpoint, this study aimed to establish how patients with COPD are treated according to the Global Initiative for Chronic Obstructive Lung Disease (GOLD) classification system and to quantify the symptom burden.Methods: Data were obtained from the Respiratory DSP, a cross-sectional survey of patients with a diagnosis of COPD consulting for routine care in France, Germany, Italy, Spain, the UK, and the USA during the third quarter of 2013. Patients’ exacerbation risk and symptom data were used for classification into GOLD groups A-D based on GOLD 2014 criteria. Prescribing practices were stratified by physician type and time since patient diagnosis.Results: A total of 903 physicians participated in the Respiratory DSP, with data from 1,641 patients included in this analysis. Most patients were classified into GOLD groups B (n=742; 45.2%) and D (n=704; 42.9%). Patients in groups A and D were most likely to be treated in line with GOLD recommendations (61.5% and 77.5%, respectively), compared with 40.1% for group B. Patients with a diagnosis within the past 12 months were more likely to be treated according to recommendations. Inhaled corticosteroids (ICSs) in combination with one or more long-acting bronchodilator were prescribed across all GOLD groups. Patterns of treatment were, in general, similar for patients treated by a primary care physician or a pulmonologist. COPD assessment test scores ≥10 indicating a high symptom burden were reported for >80% of patients.Conclusion: This analysis confirmed a high symptom burden among patients with COPD and indicates some misalignment of prescribing with GOLD recommendations, particularly regarding the role of ICS/long-acting β2-agonist (LABA) and ICS/LABA + long-acting muscarinic antagonist combinations across the different GOLD groups. Keywords: bronchodilators, COPD, treatment, GOLD group, symptom, routine care